(untitled) (Revista Paradigma, 2020)
One of the main foundations of the Welfare State is to contribute to the most unfortunate in the defense of equality from governmental programs and social benefits. However, after the enactment of the Constitution of Federative Republic of Brazil the 1988 and the extension of social rights, there is an excess of lawsuits. This article analyzes the crisis of the Constitutional State of Social Welfare and the scrambling of state functions in the face of the protagonism exercised by the Judiciary, through the possible hypotheses of increasing the judicialization of social relations, in order to (re) construct the meaning of citizenship in the search for social pacification.